Early sport specialization impact on rates of injury in collegiate and professional sport participation: A systematic review and meta-analysis - Adlou, B.; Wilson, A.; Wilburn, C.; Weimar, W. (International Journal of Sports Science & Coaching, 2024)
Early sport specialization (ESS) is prevalent among adolescent athletes aspiring for elite status. However, the impact of ESS on sports injury (SI) rates during their collegiate and professional careers remains unclear. This systematic review and meta-analysis evaluate the effect of ESS on SI rates during high-level sport participation. Data sources Search included PubMed, Web of Science, SPORTDiscus, EMBASE, Cochrane, CINAHL, ERIC, and Medline. Study selection PRISMA guidelines were followed to identify peer-reviewed articles published until 01 August 2023. Eligible studies reported numbers of athletes in collegiate and professional teams, including national, in ESS and their counterpart category, along with the portion with at least one SI. Studies on concussion or non-contact injuries, or without explicit injury reports during elite sport participation were excluded. Of 526 studies, 13 met the criteria, and 5 were included in the quantitative analysis. These studies reported SIs on collegiate and professional athletes. A total of 3087 athletes were analyzed (ESS = 45%). The overall effect showed that ESS athletes had a lower odds ratio (OR = 0.7) of a SI during high-level sport participation, but this finding was not statistically significant (p > 0.05). Results demonstrated that ESS athletes had a lower odds ratio (OR = 0.7) of a SI during elite sport participation, but the effect was not statistically significant. Articles with clear reports are scarce, and thus limit the impact of the findings in this study. High heterogeneity was evident in this analysis, largely due to lack of standardized terminology, evaluation, and data representation. Prospective studies that consider diverse athlete population of the same sport are warranted.